Efficacy and safety of flumazenil injection for the reversal of midazolam sedation after elective outpatient endoscopy. Issue 2 (15th March 2018) - Lee, Sang Pyo; Sung, In‐Kyung; Kim, Jeong Hwan; Lee, Sun‐Young; Park, Hyung Seok; Shim, Chan Sup
Abstract : OBJECTIVE: Midazolam sedation during elective endoscopy is widely performed and flumazenil is frequently administered after endoscopy to reverse sedation in clinical practice. This study aimed to investigate the safety and efficacy of flumazenil injections after elective endoscopy under midazolam sedation. METHODS: Participants who underwent an upper endoscopy under midazolam sedation were randomly divided into two groups. In group I, flumazenil was administered i.v. 10 min after the patient's transfer to the recovery room, and no antidote was injected in group II. The time of stay in the recovery room and adverse events were reviewed through the nursing records. We asked the patients about their pain and degree of satisfaction according to a visual analogue scale (VAS), their memory of the procedure, mental status and the presence of uncomfortable symptoms on the day of the procedure and the day afterwards. RESULTS: The length of stay in recovery was significantly shorter in group I than in group II. No significant differences were found in the number of patients with pain (VAS ≥1), adverse events and discomfort between the two groups. Additionally, there were no differences in the patients' memory of the procedure, satisfaction with sedation, willingness to repeat the endoscopy and mental status. CONCLUSIONS: The time in the recovery room after flumazenil administration was significantly shortened, and the use of the drug did not increase the risk of adverse events or discomfort. The use of flumazenil for reversing midazolam sedation seems to be safe and effective.